Choice of self-adjustment algorithm for the adaptive device of coherent accumulation of the reflected signal in the radar intake - S. A. Gabets; S. U. Sedyshev (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
The results of the analysis of various classes adaptive algorithms for self-adjustment of adaptive device of reflected signal coherent accumulation are presented. The basic indicators of their quality are considered. Confidential intervals of an estimation of signal’s correlation factor by adaptive trellised RLS-algorithm for various sample’s lengths are calculated.